MORPHOLOGICAL ERRORS IN NARRATIVE WRITING OF ELEVENTH GRADE STUDENTS AT MADRASAH ALIYAHNEGERI 2 PALEMBANG - Sahran Imam (Edukasi, 2016)
The objectives of the study are 1) to find out the types of morphological errors in students of MAN 2 Palembang in writing narrative composition, 2) to find out the most frequent type of morphological errors made by eleventh grade students of MAN 2 Palembang in their narrative compositions. Thirty nine students of the eleventh grade students at MAN 2 Palembang were assigned to write narrative text in English based on the topic provided by the researcher. They were asked to write text in 60 minutes. The frequencies of errors were calculated as percentage. In this thesis, the researcher used morphological errors taxonomy based on James to identify the English composition of eleventh grade students of MAN 2 Palembang. This study revealed: 1) The participants contributed noun morphology errors, verb morphology errors, and adjective morphology errors. 2) The most frequent type of morphological errors contributed by participants were ‘misselection’. The identified sources of errors were mainly from first language (L1) transfer rather than second language (L2) intrinsic difficulty. From this study, the writer believe that students’ L1 interferes their L2 in their second language learning.